2023
DOI: 10.1039/d3qm00148b
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in porous catalysts for dehydrogenation of ammonia borane

Abstract: Hydrogen emerges as alternative green energy, replacing fossil fuels due to its high gravimetric energy density, pollution free, efficiency, and renewability. Ammonia borane (AB) possessing high hydrogen density (19.6 wt.%)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 222 publications
0
6
0
Order By: Relevance
“…As a result, Co 0.8 Cu 0.2 @NC@mSiO 2 exhibited a negligible decrease in activity, with a relative intrinsic activity decline of only 0.8 % after 30 cycles in comparison with that of Co 0.8 Cu 0.2 @NC, underscoring its excellent reusability. As displayed in Figure 5d and Table S3, the stability of Co 0.8 Cu 0.2 @NC@mSiO 2 exceeded that of the majority of reported catalysts [10–22,29–34,42,43,48–75] . A negligible loss was observed for Co 0.8 Cu 0.2 @NC@mSiO 2 , as shown in Table S1.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As a result, Co 0.8 Cu 0.2 @NC@mSiO 2 exhibited a negligible decrease in activity, with a relative intrinsic activity decline of only 0.8 % after 30 cycles in comparison with that of Co 0.8 Cu 0.2 @NC, underscoring its excellent reusability. As displayed in Figure 5d and Table S3, the stability of Co 0.8 Cu 0.2 @NC@mSiO 2 exceeded that of the majority of reported catalysts [10–22,29–34,42,43,48–75] . A negligible loss was observed for Co 0.8 Cu 0.2 @NC@mSiO 2 , as shown in Table S1.…”
Section: Resultsmentioning
confidence: 71%
“…As displayed in Figure 5d and Table S3, the stability of Co 0.8 Cu 0.2 @NC@mSiO 2 exceeded that of the majority of reported catalysts. [10][11][12][13][14][15][16][17][18][19][20][21][22][29][30][31][32][33][34]42,43, A negligible loss was observed for evolved through AB hydrolysis performed using Co 0.8 Cu 0.2 @NC, Co 0.8 Cu 0.2 @NC@mSiO 2 -0.2, Co 0.8 Cu 0.2 @NC@mSiO 2 , and Co 0.8 Cu 0.2 @NC@mSiO 2 -0.6 at 298 K. (b) Comparison between the TOFs of Co 0.8 Cu 0.2 @NC@mSiO 2 and previously reported AB-hydrolyzing noble-metal-free catalysts operating at 298 K, originating from Table S2. (c) Relative intrinsic activity of Co 0.8 Cu 0.2 @NC@mSiO 2 subjected to cycling stability tests at 298 K. (d) Stability comparison between Co 0.8 Cu 0.2 @NC@mSiO 2 and previously reported AB-hydrolyzing catalysts (Relative intrinsic activity = the activity of the last cycle/the initial activity).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, typical catalysts for AB hydrolysis are derived from NM and non-NM, respectively, as described in the precedent reviews [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83]. Although NM catalysts generally exhibit high catalytic activity, their high cost and rarity make them unsuitable for large-scale industrial applications.…”
Section: Nh3bh3 + 2h2o = 3h2 + Nh4bo2mentioning
confidence: 99%
“…In recent years, one of the most effective methods for enhancing the catalytic performance of Co‐based catalysts has been the fabrication of bimetallic Co‐based alloy catalysts by introducing other cost‐effective and earth‐abundant transition metals, such as Cu, Ni, and Fe [27–31] . Among these, Co−Cu alloy catalysts have been considered ideal candidates for accelerating hydrogen evolution from AB hydrolysis, owing to the synergistic effects of their Co−Cu bimetallic components [30–32] . Previous studies have revealed that Co−Cu alloy catalysts can be synthesized either by following a step‐by‐step reduction strategy, or via MOFs pyrolysis [13,17,33] .…”
Section: Introductionmentioning
confidence: 99%